Safety and tolerability of a 90‐minute rapid infusion of Sandoz biosimilar rituximab in B‐cell lymphoproliferative disorders in a real‐world setting. Issue 2 (24th November 2022) - Muntañola, Ana; Arguiñano‐Pérez, José María; Dávila, Julio; de Villambrosia, Sonia González; Carpio, Cecilia; Jiménez‐Ubieto, Ana; Salar, Antonio
Abstract: Although rituximab is generally well‐tolerated, infusion‐related reactions (IRRs) are common with the initial dose when administered intravenously according to standard recommendations. To prevent IRRs, premedication and low‐speed infusion rates have been recommended. Consequently, intravenous (i.v.) infusion of rituximab can become a labor‐intensive process. Rapid i.v. rituximab infusion over 90 min has demonstrated a favorable safety profile for the second and subsequent infusions during the course of therapy. The aim of this study was to investigate the safety and tolerability of 90‐min rapid infusion of Sandoz rituximab biosimilar (SDZ‐RTX) for patients with CD20+ lymphoma or chronic lymphocytic leukemia (CLL). We retrospectively reviewed all patients with CD20+ lymphoma or CLL who received SDZ‐RTX infusions in 90 min from July 2019 to July 2021 at seven Spanish hospitals. The primary end point was the incidence of IRRs. We identified 124 patients and 576 rapid administrations of SDZ‐RTX, with an average of five rapid infusions per patient. Most rapid infusions of SDZ‐RTX were in combination with CHOP/CHOP‐like therapy (48.4%), followed by SDZ‐RTX alone (15.1%), in combination with bendamustine (14.5%), or with other regimens (22%). The 90‐min SDZ‐RTX infusion schedule was well‐tolerated with no grade 3/4 IRRs. The incidence of any grade IRR during the first rapid infusion was 1% (5 grade 1 IRRs and 1 grade 2 IRR). In conclusion, rapid 90‐min i.v. administration of SDZ‐RTX for the second and subsequent infusions during the course of therapy is well‐tolerated in patients with CD20+ lymphoma or CLL.